Pengaruh Relokasi dan Modal Usaha Terhadap Tingkat Pendapatan Pedagang Pasar Angso Duo Kota Jambi - M.Firmansyah; Ambok Pangiuk (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2022)
This study determine and analyze the effect of relocation and venture capital on the income level of Angso Duo market traders in Jambi City. Quantitative approach research and multiple linear regression data analysis. The research sample is 87 Angso Duo market traders. The results of the t-test of relocation (X1) on income (Y) partially have a positive effect on the income level of market traders. evidenced by a significant 0.000 < 0.0005 tcount > t table, which is 3.800 > 1.667 that relocation has a positive effect because Ha is accepted and H0 is rejected which states that there is a significant positive effect between the relocation variable (X1) on income (Y). The results of the t-test Business Capital (X2) on income (Y) partially has no effect and is not significant on the income level of market traders. evidenced by the significant value of 0.692 > 0.005 and the value of t count > t table 0.397 < 1.667. concluded that Ha is rejected and H0 is accepted stating that there is no and no significant effect between the variables of venture capital (X2) on income (Y). The results of the F test are known that the significance value for the effect of relocation (X1) and working capital (X2) simultaneously on the income of traders (Y) is 0.001 < 0.005 and the value of Fcount > Ftable (8.049 > 3.105). Concluded that H0 is rejected, which means that there is a significant effect between relocation and working capital simultaneously on the income of the Angso Duo Jambi market traders. The value of Adjusted R Square is 0.141 or 14.1%, which means that income of market traders influenced relocation and business capital of 14.1% while the remaining 85.9% influenced by other variables not examined in this research model. Kata kunci : Market Relocation, Business Capital, Income.